2020
DOI: 10.3390/cancers12051162
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer and Probiotics: Are Bugs Really Drugs?

Abstract: Colorectal cancer (CRC) is one of the most common types of cancer worldwide. There are many factors that predispose a patient to the disease such as age, family history, ethnicity, and lifestyle. There are different genetic factors and diseases that also increase a person’s risk for developing CRC. Studies have found associations between gut microbiome and the risk for developing versus protection against CRC. Normal gut microbiome aid in daily functions of the human body such as absorption, metabolism, detoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 127 publications
(234 reference statements)
0
14
1
1
Order By: Relevance
“…Colorectal cancer is a heterogeneous disease associated with genetic mutations, age, family history, ethnicity, and lifestyle. 273 278 The downregulation of GSDMC led to significant decreases in the proliferation and of colorectal cancer cells, while GSDMC overexpression promoted cell proliferation, tumorigenesis suggesting that GSDMC may be a promising therapeutic target in colorectal cancer. 54 GSDMD was downregulated in carcinoma cells, while it was slightly overexpressed in normal colorectal epithelial cells.…”
Section: Role Of Pyroptosis In Tumorsmentioning
confidence: 99%
“…Colorectal cancer is a heterogeneous disease associated with genetic mutations, age, family history, ethnicity, and lifestyle. 273 278 The downregulation of GSDMC led to significant decreases in the proliferation and of colorectal cancer cells, while GSDMC overexpression promoted cell proliferation, tumorigenesis suggesting that GSDMC may be a promising therapeutic target in colorectal cancer. 54 GSDMD was downregulated in carcinoma cells, while it was slightly overexpressed in normal colorectal epithelial cells.…”
Section: Role Of Pyroptosis In Tumorsmentioning
confidence: 99%
“…The continuous production and secretion of pro-inflammatory cytokines such as IL-6, IL-17, and TNF have been associated with human colonic carcinogenesis [ 47 ]. According to Lamichhane et al (2020) [ 48 ], probiotics administration can effectively modulate immune functions in the gut by reducing the production of tumor-promoting cytokines. The present study showed that the highest concentrations of the pro-inflammatory cytokines IL-6 and IL-17 were found in the colon tissue of animals subjected to DMH treatment only (GNI group), whereas the intervention with the probiotic candidate L. paracasei DTA81 reduced significantly the levels of both cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Although Caspase 3 levels did not differ among the experimental groups, additional pro-apoptotic genes, such as Bax and Caspase 9, may also contribute to the balance between proliferation and apoptosis of tumor cells. With regard to L. paracasei strains and apoptosis’ regulation, their activities are attributed to different mechanisms such as by stimulation of proapoptotic genes [ 48 ], the promotion of cell cycle arrest, and calreticulin translocation via the generation of ROS, observed for L. paracasei M5L [ 43 ], and by modulating the expression of specific Bcl-2 family proteins as hypothesized to the strain L. paracasei K5 [ 83 ]. Immunomodulation is another possible mechanism that contributes to the proapoptotic activity induced by probiotics, especially increased TNF production [ 67 ], as observed in the present study for the LGG group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although synbiotic supplementation with Bifidobacterium lactis and resistant starch produced unique changes in the fecal microflora in another study of patients with colorectal cancer, it did not significantly alter any other fecal, serum, or epithelial biomarkers [ 73 ]. The authors of this study underscored the need to consider the patient’s family history and lifestyle, including diet, smoking, and other factors, before treatment with probiotics or synbiotics, and that further, in-depth research should be undertaken to gain a better understanding of the clinical value of these agents in colorectal cancer [ 74 ].…”
Section: Interplay Between the Gut Microbiome And Radiotherapy Toxicimentioning
confidence: 99%